STUDI PEMANTAUAN DAN EVALUASI TATA RUANG DI KABUPATEN POSO - Amar, Amar (MEKTEK, 2005)
Research aim to monitoring and evaluating differences in spatial planning product that it arranged with existing conditions in Kabupaten Poso. The method was survey method with quantify analysis approach to different counts in spatial planning monitoring aspects in to three groups populations, land use, and space structures. Analysis result showed for all spatial planning monitoring aspects have very significant differences and have not relevant with spatial planning product in Kabupaten Poso condition, it also influenced by regional wide become two regions as Kabupaten Poso and Kabupaten Tojo Unauna, so spatial planning product must be totally revised.